PENGARUH IKLIM ORGANISASI DAN LOYALITAS KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Fitriani, Ni Wayan; Manuati Dewi, I Gusti Ayu (E-Jurnal Manajemen, 2017)
This study aims to describe the influence of organizational climate and job loyalty to organizational citizenship behavior at the Hotel Santika Purwokerto. Respondents are all employees contracts that amounted to 77 people. The sampling method using saturated sampling (penyamplingan saturated). The data collection is done by distributing questionnaires to measurement using a Likert Scale to measure the 18-point declaration of 3 variables of the study. The analysis technique used is multiple linear regression. The analysis showed that organizational climate positive and significant effect on organizational citizenship behavior. Besides loyalty employment is also positive and significant effect on organizational citizenship behavior. The company must pay attention to the organizational climate and employee loyalty to improve organizational citizenship behavior.
Keywords: organizational climate, job loyalty, organizational citizenship behavior